The Effects of a 14-week Physical Preparation Programme on Developing Adolescent Seam Bowlers in Cricket - Scott Hislen; Mykolas Kavaliauskas; Brendon Ferrier; Cedric English (International Universities Strength and Conditioning Association, 2023)
From a physical demand point of view, fast bowling is reported to be the most demanding position in cricket. Unsurprisingly, physical preparation has been shown to enhance performance and reduce injury risk in adult seam bowlers. However, limited research has been conducted into the effects of physical preparation in youth developing seam bowlers.   Therefore,the purpose of this study was to determine the effectiveness of a 14-week physical preparation programme on the developing seam bowler.   Six developing academy-level seam bowlers (18.1 ± 1.1 years) completed a 14-week periodised bowling- specific programme. Pre/post tests across various physical qualities (strength, power, muscular endurance, speed and aerobic capacity) and bowling performance (upper arm angular velocity) were recorded. Changes from pre-post testing were measured using a paired sample t-test (p ≤ 0.01) and effect sizes.   Post 14-week intervention, group relative changes showed improvement in strength (+8%), power (+2%), muscular endurance (+45%), speed (-6%) and aerobic capacity (+3). Within participant group there was no significant difference (p = 0.77) in upper arm angular velocity.   Positive improvements in all physical qualities were recorded post intervention. Interestingly, this did not translate into an increase in upper arm angular velocity. Future research should consider the benefits of mixed-methods research approach, where the technical and physical characteristics are closely aligned within developmental programmes, to enhance performance and reduce injury in this population.